Konsepsi Materi Muatan Piagam Madinah dan UUD 1945 : Hak Kebebasan Memeluk Agama - Rifky Mohamad Ramdani (Asian Journal of Law and Humanity, 2021)
The right to freedom of religion is a right that must be regulated and guaranteed by the state as a fundamental and universal human right inherent in human beings. This study aims to analyze the differences in the regulation of the right to religious freedom in the Medina Charter and the 1945 Constitution of the Republic of Indonesia and their application. This normative juridical research uses a legal and conceptual approach. The results of the study indicate that both the Medina Charter and the 1945 Constitution of the Republic of Indonesia have contained provisions regarding the right to freedom of religion, but there are fundamental differences between the two, namely in terms of the difference in regulation between religion and belief. The 1945 Constitution of the Republic of Indonesia stipulates that there are differences between religion and belief, while in the Medina Charter there is no different arrangement between religion and belief. The 1945 Constitution of the Republic of Indonesia only regulates rights, while obligations are not regulated and must be carried out according to their respective beliefs. The conception of differences in regulation between religion and belief in the 1945 Constitution of the Republic of Indonesia can be an opportunity to cause religious conflict in Indonesia.